Computational drug treatment simulations on projections of dysregulated protein networks derived from the myelodysplastic mutanome match clinical response in patients. (January 2017) - Drusbosky, Leylah; Medina, Cindy; Martuscello, Regina; Hawkins, Kimberly E.; Chang, Myron; Lamba, Jatinder K.; Vali, Shireen; Kumar, Ansu; Singh, Neeraj Kumar; Abbasi, Taher; Sekeres, Mikkael A.; Mallo, Mar; et al.
Highlights: Computer modeling of MDS mutanome predicts response to HMAs with 80–100% accuracy. Modeling of MDS mutanome revealed biomarkers for drug response. Modeling of MDS mutanome unveils resistance pathways to drug therapies. Protein network mapping reveals potential targets of drug therapy. Abstract: Although the majority of MDS patients fail to achieve clinical improvement to approved therapies, some patients benefit from treatment. Predicting patient response prior to therapy would improve treatment effectiveness, avoid treatment-related adverse events and reduce healthcare costs. Three separate cohorts of MDS patients were used to simulate drug response to lenalidomide alone, hypomethylating agent (HMA) alone, or HMA plus lenalidomide. Utilizing a computational biology program, genomic abnormalities in each patient were used to create an intracellular pathway map that was then used to screen for drug response. In the lenalidomide treated cohort, computer modeling correctly matched clinical responses in 37/46 patients (80%). In the second cohort, 15 HMA patients were modeled and correctly matched to responses in 12 (80%). In the third cohort, computer modeling correctly matched responses in 10/10 patients (100%). This computational biology network approach identified GGH overexpression as a potential resistance factor to HMA treatment and paradoxical activation of beta-catenin (through Csnk1a1 inhibition) as a resistance factor to lenalidomide treatment. We demonstrate that a computational technology is able to map the complexity of the MDS mutanome to simulate and predict drug response. This tool can improve understanding of MDS biology and mechanisms of drug sensitivity and resistance.